HOW FRAUD HEXAGON MODEL ON FINANCIAL STATEMENT FRAUD IN ENERGY SECTOR COMPANIES? - Hakim, Mohamad Zulman; Hamdani; Hustna Dara Sarra; Alvina Anggraini; Gadis Ayu Rizky Darmala; Elsa Audia Utami (ZILLZELL MEDIA PRIMA, 2024)
Financial statement fraud is a discrepancy between the application of accounting principles and the preparation of financial statements with the aim of deceiving users of financial statements This study aims to analyze the effect of Hexagon Fraud on financial statement fraud. There are 10 variables used, namely financial targets, financial stability, change of directors, monitoring, ideal condition of the company, change of auditor, photo of the CEO, government projects, political connections, managerial ownership. Financial statement fraud is measured using the Beneish M-Score Model. The samples in this study are energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021 with the number of samples used being 50 companies with 100 units of analysis taken based on the purposive sampling method. Data analysis in this study used panel data regression analysis with the EViews 13 analysis tool. The results of this study show that a company's Financial Target has an influence on the potential for financial statement fraud. Meanwhile, financial stability, change of directors, monitoring, ideal condition of the company, change of auditor, CEO photo, government projects, political connections, managerial ownership have no influence on the potential for financial statement fraud.